Kazak faecal microbiota transplantation induces short-chain fatty acids that promote glucagon-like peptide-1 secretion by regulating gut microbiota in db/db mice - Xue Han; Ye Wang; Peipei Zhang; Manli Zhu; Ling Li; Xinmin Mao; Xiaoting Sha; Linlin Li (Taylor & Francis Group, 2021)
Context Faecal microbiota transplantation (FMT) from Kazak individuals with normal glucose tolerance (KNGT) significantly reduces plasma glycolipid levels in type 2 diabetes mellitus db/db mice. However, the mechanism behind this effect has not been reported. Objective To study the mechanism of improved glycolipid disorders in db/db mice by FMT from a KNGT donor. Materials and methods The normal diet group consisted of db/m mice orally administered 0.2 mL phosphate buffer saline (PBS) (db/m + PBS). For the db/db + PBS (Vehicle) and db/db + KNGT (FMT intervention group) groups, db/db mice received oral 0.2 mL PBS or faecal microorganisms from a KNGT donor, respectively. All mice were treated daily for 0, 6 or 10 weeks. Faecal DNA samples were sequenced and quantified using 16S rRNA gene sequencing and RT-qPCR, respectively. Short-chain fatty acid (SCFA) levels in the mouse faeces were determined by gas chromatography. G protein-coupled receptor 43 (GPR43) and glucagon-like peptide-1 (GLP-1) expression levels were determined. Results FMT intervention significantly increased the relative abundance of Bacteroides uniformis (0.038%, p < 0.05). Clostridium levels (LogSQ) were increased (p < 0.01), while Mucispirillum schaedleri levels (LogSQ) were decreased (p < 0.01). Acetate and butyrate levels in the faeces were significantly increased (acetate; butyrate: 22.68 ± 1.82 mmol/L; 4.13 ± 1.09 mmol/L, p < 0.05). GPR43 mRNA expression and GLP-1 protein expression increased in colon tissue (p < 0.05). Discussion and conclusions Mechanistically, FMT-KNGT could improve glycolipid disorders by changing the bacterial composition responsible for producing SCFAs and activating the GPR43/GLP-1 pathway.